2D image reconstruction in the stochastic MR-simulation with gridding and back projection method - Sediono, Wahju (IECI, 2000)
Stochastic magnetic resonance imaging (MRI) offers the possibility of significant power reduction. One important aspect of the MRI is two-dimensional image reconstruction. It is therefore very useful to evaluate 2D image reconstruction of stochastic imaging in a computer simulation.